2011
DOI: 10.1039/c1nr10429b
|View full text |Cite
|
Sign up to set email alerts
|

(AuAg)144(SR)60 alloy nanomolecules

Abstract: (Au-Ag)(144)(SR)(60) alloy nanomolecules were synthesized and characterized by ESI mass spectrometry to atomic precision. The number of Ag atoms can be varied by changing the incoming metal ratio and plateaus at ∼60. UV-vis data demonstrates that the electronic structure of the nanomolecules can be tuned by incorporation of silver atoms. Based on the proposed 3-shell structure of Au(144)(SR)(60), we hypothesize that the Ag atoms are selectively incorporated in to the symmetry equivalent 60-atom shell-having Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
187
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(193 citation statements)
references
References 34 publications
5
187
1
Order By: Relevance
“…More recently, Dass et al [94,95] showed a very interesting synthetic method, encompassing the evolution from molecule-like to plasmon resonance systems, as a function of the number of atoms in the gold cluster. For instance, they have shown that the clusters Au 25 (SR) 18 , Au 38 (SR) 24 , Au 102 (SR) 44 and Au 144 (SR) 60 behave as ultra-small (< 2 nm) thiolated gold nanoparticles, but resembling molecules, while Au 329 (SR) 84 shows a plasmon resonance peak (SR = organothiol).…”
Section: Gold Nanoparticlesmentioning
confidence: 99%
“…More recently, Dass et al [94,95] showed a very interesting synthetic method, encompassing the evolution from molecule-like to plasmon resonance systems, as a function of the number of atoms in the gold cluster. For instance, they have shown that the clusters Au 25 (SR) 18 , Au 38 (SR) 24 , Au 102 (SR) 44 and Au 144 (SR) 60 behave as ultra-small (< 2 nm) thiolated gold nanoparticles, but resembling molecules, while Au 329 (SR) 84 shows a plasmon resonance peak (SR = organothiol).…”
Section: Gold Nanoparticlesmentioning
confidence: 99%
“…[10] However, synthesis of atomically precise alloy QCs of various compositions is a challenge. [11] Murray et al synthesized Pd@Au 24 (SR) 18 which was further studied by Negishi et al [ 11b] Negishi et al isolated PdAu 24 (SR) 18 .…”
mentioning
confidence: 98%
“…Stable gold cluster molecules of the type Au 11 , [1a] Au 13 , [1b,c] and Au 55 , [1d] have been fascinating and were some of the early molecular nanosystems synthesized. Quantum phenomena such as Coulomb blockade were demonstrated with them.…”
mentioning
confidence: 99%
“…Moreover, high stability leads to high reproducibility of experiments. Many groups have studied this compound [12][13][14][15][16] with varying thiolate ligands and, more recently, with noble-metal compositions varying between pure gold and different Au-Ag 17 and Au-Cu 18 alloys. These clusters are notable for their compact symmetrical structure, well-defined electrical capacitance, and optical and electronic properties.…”
mentioning
confidence: 99%